Wake Behavior behind Turbine Cascades in Compressible Two-Dimensional Flows - Rainer Kurz (International Journal of Rotating Machinery)
The goal of the paper is to describe wake parameters of wakes from turbine cascades in compressible flows especially in planes where the leading edge of the following blade row would be located. Data from experiments with turbine cascades in compressible flow will be used to derive a theoretical approach which describes the wake growth and the recovery of the velocity deficit. The theory is based on similarity assumptions. The derived equations depend on simple and readily available parameters such as overall losses, exit angle, and Mach or Laval number. In compressible turbine flows, the influence of the inviscid flow field is of great importance. In this paper, an approach to take this influence into account when determining the behavior of the wake is presented. Correlations for basic characteristics of wakes in compressible flows are not readily available. Such correlations are necessary as input to unsteady flow and heat transfer calculation procedures for turbomachine blades. Based on available data on wake behavior in the compressible flow behind turbine blades, the correlations presented describe the wake behavior from the trailing edge to the confluence of the wakes of adjacent blades.